Obesity hypoventilation syndrome treated with non‐invasive ventilation: Is a switch to CPAP therapy feasible?. Issue 4 (9th October 2019) - Arellano‐Maric, Maria P.; Hamm, Christine; Duiverman, Marieke L.; Schwarz, Sarah; Callegari, Jens; Storre, Jan H.; Schmoor, Claudia; Spielmanns, Marc; Galetke, Wolfgang; Windisch, Wolfram
ABSTRACT: Background and objective: Obesity hypoventilation syndrome (OHS) can be treated with either continuous positive airway pressure (CPAP) or non‐invasive ventilation (NIV) therapy; the device choice has important economic and operational implications. Methods: This multicentre interventional trial investigated the safety and short‐term efficacy of switching stable OHS patients who were on successful NIV therapy for ≥3 months to CPAP therapy. Patients underwent an autotitrating CPAP night under polysomnography (PSG); if the ensuing parameters were acceptable, they were sent home on a fixed CPAP for a 4–6‐week period. It was hypothesized that blood gas analysis, PSG parameters and lung function tests would remain unchanged. Results: A total of 42 OHS patients were recruited, of whom 37 patients were switched to CPAP therapy. All patients had a history of severe obstructive sleep apnoea syndrome; chronic obstructive pulmonary disease (COPD) (Global Initiative for Obstructive Lung Disease (GOLD) I/II) was present in 52%. Regarding the primary outcome, 30 of 42 patients (71%, 95% CI: 55–84%) maintained daytime partial pressure of carbon dioxide (PaCO2 ) levels ≤45 mm Hg after the home CPAP period. There was no further impairment in quality of life, sleep parameters or lung function. Interestingly, 24 patients (65%) preferred CPAP as their long‐term therapy, despite the high pressure levels used (mean: 13.8 ± 1.8 mbar). After the CPAP period, 7 of 37 patients were categorized as CPAP failure, albeit only due to mild hypercapnia (mean: 47.9 ± 2.7 mm Hg). Conclusion: It is feasible to switch most stable OHS patients from NIV to CPAP therapy, a step that could significantly reduce health‐related costs. The auto‐adjusted CPAP device, used in combination with the analysis of the PSG and capnometry, is a valid titration method in OHS patients. Abstract : A total of 42 obesity hypoventilation syndrome (OHS) patients undergoing home non‐invasive ventilation (NIV) therapy were switched to a 4−6‐week period of continuous positive airway pressure (CPAP) therapy. This protocol proved to be safe and well‐tolerated by patients. There was no impairment in quality of life, sleep parameters or lung function. These data could significantly reduce costs for the health system. See related Editorial